Formulation of Stunting Prevention Supplements Based on Spinach, Silk Tofu and Eggs in Gunungsari Village, Pemalang - Pragita, Amellia; Fauziah, Hasna Ainun; Rose, Ladya Cheryl; Habibi, Iqbal; Fadillah, Azra Maidha Nur; Aryana, Salsa Bella; Nurrohmah, Eka; Prasta, Arya Indra; Sundari, Diva Tri; Sahrani, Putri Serlia; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
Stunting is still a public health problem in Indonesia even though its prevalence has decreased from 24.4% in 2021 to 19.8% in 2024. This figure is still above the WHO threshold of 20% and the national target of 14%. In Pemalang Regency, the prevalence of stunting decreased from 10.35% in 2021 to 8.0% in 2023, but increased again to 10.3% in early 2024 due to low coverage of exclusive breastfeeding, incomplete basic immunization, and low consumption of nutritious supplementary foods in toddlers. This research aims to develop and introduce additional food formulations based on spinach juice, silk tofu, and eggs as a preventive measure against stunting in toddlers. The program was carried out in Gunungsari Village, Pemalang, through nutrition education, leaflet distribution and additional food distribution. Analysis of nutritional content shows that this formulation is rich in quality protein, iron, vitamin A, calcium, and vitamin B12. The conclusion is that this dietary supplement formulation has the potential to be integrated into community-based nutrition programs, especially as a prevention strategy in areas with low but fluctuating stunting prevalence.